Comparing helpful and hindering processes in good and poor outcome cases: A qualitative metasynthesis of eight Hermeneutic Single Case Efficacy Design studies. (3rd April 2022) - Stephen, Susan; Bell, Laura; Khan, Maha; Love, Ruth; Macintosh, Hannah; Martin, Melanie; Moran, Rebecca; Price, Emily; Whitehead, Brigid; Elliott, Robert
Abstract: Objective: We tested qualitative metasynthesis of a series of Hermeneutic Single Case Efficacy Design (HSCED) studies as a method for comparing within-session processes that may explain good and poor therapeutic outcome. Method: We selected eight HSCED studies according to change in clients' scores on the Strathclyde Inventory (SI), a brief self-report instrument used to measure outcome in person-centered psychotherapy. Four of the case studies investigated the experience of clients whose pre–post change in SI scores showed improvement by the end of therapy, and the other four focused on clients whose change in SI scores indicated deterioration. We conducted a qualitative metasynthesis, adopting a generic descriptive-interpretive approach to analyze and compare the data generated by the HSCED studies. Results: In contrast to improvers, deteriorators appeared to be less ready to engage in therapeutic work at the beginning of therapy, and found the process more difficult; their therapists were less able to respond to these difficulties in a responsive, empathic manner; deteriorators were less able to cope successfully with changes of therapist and, eventually, gave up on therapy. Conclusion: We found that our qualitative metasynthesis of a series of HSCED studies produced a plausible explanation for the contrasting outcomes that occurred.